The Experience of a Multidisciplinary Clinic in the Management of Early-Stage Breast Cancer Patients Receiving Trastuzumab Therapy: An Observational Study - Susan Dent; Sean Hopkins; Nadine Graham; Christopher Johnson; Angeline Law; Michelle Campbell; Freya Crawley; Kathleen Allen; Michele Turek (Cardiology Research and Practice)
Background. We established a dedicated cardiac oncology clinic in 2008 for the rapid diagnosis and treatment of cardiotoxicity related to cancer therapy. In this retrospective observational study, we report on clinical outcomes in women with early-stage breast cancer (EBC) referred to this clinic. Methods. Patients with EBC treated with chemotherapy/trastuzumab and referred between October 2008 and December 2010. Data included patient demographics, staging, cancer treatment/completion, dose delays, left ventricular ejection fraction (LVEF) and cardiac treatment. Results. Forty eight patients: median age 55.5 years, stage I/II disease (77%) and HER-2 positive (98%). The majority of women (n=32) were referred for decreases in LVEF (from baseline). Overall, 37 (77%) patients experienced at least one drop in LVEF while on treatment, of which 22 patients (59%) experienced a ≥10 percentage point drop. The majority of patients (30/37; 81%) experienced declines in LVEF while on trastuzumab. Interventions included trastuzumab delays (n=16/48; 33%) and cardiac medication (12/48: 25%). A total of 81% of patients completed ≥90% of trastuzumab therapy and 15% of patients discontinued therapy due to cardiotoxicity. Conclusion. The majority of patients referred to our clinic completed therapy. Further studies are needed to determine the impact of this multidisciplinary approach on treatment completion and cardiac outcomes.